Unilateral climate Policy and the Green Paradox: Extraction Costs matter - Gilbert Kollenbach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
To analyze the effect of unilaterally tightened climate policies, we augment the two country model of Hoel (2011) with fossil fuel extraction costs. It turns out that a tighter climate policy of the country with the initially stricter policy causes neither a weak nor a strong green paradox if the fossil fuel stock is sufficiently small. In case of a tighter climate policy in the country with the initially laxer policy, a weak green paradox depends on the price-elasticity of energy demand.
Keywords: Q41; Q42; Q54; Q58; 330